2011
DOI: 10.1007/s10530-011-0009-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in Malaysian oysters: taxonomic ambiguities and evidence of biological invasion

Abstract: Genetic diversities in two cultured oyster species, Crassostrea iredalei (Faustino 1932) and Crassostrea belcheri (Sowerby 1871) were assessed using a 581-nucleotide fragment of the mtDNA cytochrome oxidase subunit 1 (CO1) gene. A total of 103 C. iredalei individuals and 120 C. belcheri from 12 populations were sampled along the coast of Malaysia. Trees of unique haplotype samples generated based on Neighbor-Joining (NJ) algorithm revealed that many individuals had been misidentified and did not cluster with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…The inter-specific variation of 16.2 % in the current study is concordant with the earlier study, but our intra-specific variation was markedly different. The current study recorded intra-specific variation of 0.6 % to 0.9 %, which was consistent with a study on Malaysian oysters (Suzana et al, 2011) and deep-sea clams (Liu and Zhang, 2018), which observed values ranging from 0.1 % to 1.1 % and 0.0 % to 2.66 %, respectively. Intra-specific variation in this present study was also in concordance with a comprehensive study of four marine bivalve genera that recorded an intra-species variation of 0.0 % to 3.2 % (Mikkelsen et al, 2007).…”
Section: Species Identificationsupporting
confidence: 92%
“…The inter-specific variation of 16.2 % in the current study is concordant with the earlier study, but our intra-specific variation was markedly different. The current study recorded intra-specific variation of 0.6 % to 0.9 %, which was consistent with a study on Malaysian oysters (Suzana et al, 2011) and deep-sea clams (Liu and Zhang, 2018), which observed values ranging from 0.1 % to 1.1 % and 0.0 % to 2.66 %, respectively. Intra-specific variation in this present study was also in concordance with a comprehensive study of four marine bivalve genera that recorded an intra-species variation of 0.0 % to 3.2 % (Mikkelsen et al, 2007).…”
Section: Species Identificationsupporting
confidence: 92%
“…This oyster inhabits mangroves and estuaries in southern Thailand, both the Gulf of Thailand and the Andaman Sea, and Surathanee, Songkhla, Pangnga and Ranong provinces (Klinbunga et al 2005). This species has high market demand in comparision with other oyster species (Suzana et al 2011).…”
mentioning
confidence: 99%
“…A median joining haplotype network was generated from the mitochondrial COI sequence data using PopART [69, 70] with the default settings. Sequences of S. echinata from previous studies ( n = 21) [32, 71] were obtained from GenBank and also included in the network analyses. Sampling sites of these sequences include Semporna in Malaysia, Taiwan, and Taketomi Island in Japan (coordinates listed in Fig.…”
Section: Methodsmentioning
confidence: 99%